Pengaruh Self Control dan Self Regulated Learning Terhadap Prestasi Belajar Siswa pada Mat - Feby Wahyuni (UIN Fatmawati Sukarno Bengkulu, 2023)
The purpose of this studi is to find out: 1) The effect of self control on student achievement in the subject of Islamic Religious Education at SMK Negeri 5 Bengkulu City, 2) The effect of self regulated learning on student achievement in the subject of Religious Education. Islam at SMK Negeri 5 Bengkulu City, 3) The effect of self control and self regulated learning on student achievement in Islamic Religious Education subjects at SMK Negeri 5 Bengkulu City. This studies uses quantitative type of research with an ex post facto approach. The population of this studies amounted to 564 students, a sample of 85 students. The sampling technique used was probability sampling with the type of proportionate stratified random sampling. Data collection techniques using questionnaires, documentation, and observation. The results showed that: 1) There was a significant influence between self control (X1) on student achievement in Islamic Religious Education subjects (Y) at SMK Negeri 5 Bengkulu City. This can be seen from the value of tcount> ttable (2.124 > 1.988) with a regression coefficient of 0.134 which contributes 13.4% to student learning achievement (Y), 2) There is a significant effect between self regulated learning (X2) on learning achievement students in the subject of Islamic Religious Education (Y) at SMK Negeri 5 Bengkulu City. This can be seen from the value of tcount> ttable (1.997 > 1.988) with a regression coefficient of 0.114 which contributes 11.4% to student learning achievement (Y), 3) There is a significant effect between self control (X1) and self regulated learning (X2) on student achievement (Y) at SMK Negeri 5 Bengkulu City. This can be seen from the value of Fcount> Ftable (4.627 > 3.10) with a coefficient of determination of 0.079 which contributes 7.9% to student achievement (Y), or it can be seen from the multiple linear regression equation Y = 66.652 + 0.134X1 + 0.114X2 + 0.05.